Teachers' views of constructivist theory: A qualitative study illuminating relationships between epistemological understanding and music teaching practice. (May 2014) - Cleaver, David; Ballantyne, Julie
While constructivist theory is widely promoted in pre-service music teacher education, there has been a lack of research conducted to reveal the ways in which the theory is individually personalized, then subsumed, translated and adopted into in-service classroom teaching practice. To address this shortfall, this article explores some of the ways that music teachers individually apply their understanding of the philosophically generated ideas and the cognitive concepts and principles that are broadly regarded as "constructivist." In seeking to contribute to professional dialogue and debate surrounding this matter, this study seeks to illuminate how a small sample of music teachers engages both theoretically and practically with constructivist views of learning. Using a qualitative approach, the researchers incorporated staged, informal interviews with invited teacher participants. Preliminary analyses of interview data were returned to the participants for review and further commentary. This process was designed to contribute to both the trustworthiness of representation and to enhance the transactional process between participants and researchers. The commentaries are designed to problematize issues, raise points for discussion and the article concludes with implications for practice in schools and universities.